How Do Students Believe in Their Mathematical Abilities? An Analysis of Applied Mathematics Problems in High School - Fakhrunisa, Fauziah; Juandi, Dadang; Hasanah, Aan (Universitas Sebelas Maret, 2022)
This study aims to describe the profile of students’ belief about mathematics related to applied mathematical problems. The purpose-designed survey method was used in this study. There were 24 high school students who were respondents in this study. Each respondent is given access to a google form consisting of 28 statements with a Likert scale response and seven open-ended questions. Finding result were analyzed by carrying out several stages, namely data reduction, data presentation, verification and drawing conclusions. Based on the data obtained, it can be concluded that the profile of students' belief about mathematics to be good in terms of believing that mathematics is a science that can be applied to various activities in real life. However, they tend to lack understanding of what is meant by applied mathematical problems, as a result of a lack of confidence in their mathematical abilities. Overall, the learning process carried out by the teacher in the classroom also affects the students’ belief about mathematics profile. This research is expected to provide a broader understanding of the strengths and weaknesses of students in terms of belief about mathematics related to applied mathematical problems.